Employee Engagement, Employee Satisfaction, and Employee Empowerment and Their Influence on Productivity in MSMEs - Sihite, Mislan; Jusup, Sri Meike; Ilham, Rachmad; Widayati, Tri (International Journal of Business, Law, and Education, 2024)
Employee productivity is a critical determinant of organizational success, particularly for micro, small, and medium enterprises (MSMEs) that often operate with limited resources. This study investigates the influence of employee engagement, satisfaction, and empowerment on productivity in MSMEs, utilizing a quantitative approach with data collected from 300 employees in Indonesia. Descriptive statistics, correlation analysis, and multiple regression analyses were employed to examine these relationships. The results indicate that all three factors significantly and positively impact productivity, with engagement serving as a mediating variable between satisfaction and productivity, as well as between empowerment and productivity. The findings underscore the importance of a holistic approach in managing human resources to enhance organizational performance. Practical implications suggest that MSMEs can improve productivity by fostering an environment that simultaneously enhances engagement, satisfaction, and empowerment. These results provide valuable insights for MSME managers and policymakers in developing strategies to sustain growth and competitivenes.